A novel nematode effector suppresses plant immunity by activating host reactive oxygen species‐scavenging system. Issue 3 (20th October 2015) - Lin, Borong; Zhuo, Kan; Chen, Shiyan; Hu, Lili; Sun, Longhua; Wang, Xiaohong; Zhang, Lian‐Hui; Liao, Jinling
Summary: Evidence is emerging that plant‐parasitic nematodes can secrete effectors to interfere with the host immune response, but it remains unknown how these effectors can conquer host immune responses. Here, we depict a novel effector, MjTTL5, that could suppress plant immune response. Immunolocalization and transcriptional analyses showed that MjTTL5 is expressed specifically within the subventral gland of Meloidogyne javanica and up‐regulated in the early parasitic stage of the nematode. Transgenic Arabidopsis lines expressing MjTTL5 were significantly more susceptible to M. javanica infection than wild‐type plants, and vice versa, in planta silencing of MjTTL5 substantially increased plant resistance to M. javanica . Yeast two‐hybrid, coimmunoprecipitation and bimolecular fluorescent complementation assays showed that MjTTL5 interacts specifically with Arabidopsis ferredoxin : thioredoxin reductase catalytic subunit (AtFTRc), a key component of host antioxidant system. The expression of AtFTRc is induced by the infection of M. javanica . Interaction between AtFTRc and MjTTL could drastically increase host reactive oxygen species‐scavenging activity, and result in suppression of plant basal defenses and attenuation of host resistance to the nematode infection. Our results demonstrate that the host ferredoxin : thioredoxin system can be exploited cunningly by M. javanica, revealing a novel mechanism utilized by plant–parasitic nematodes to subjugate plant innate immunity and thereby promoting parasitism.